Polyplex-mediated inhibition of chemokine receptor CXCR4 and chromatin-remodeling enzyme NCOA3 impedes pancreatic cancer progression and metastasis. (September 2016) - Wang, Yan; Kumar, Sushil; Rachagani, Satyanarayana; Sajja, Balasrinivasa R.; Xie, Ying; Hang, Yu; Jain, Maneesh; Li, Jing; Boska, Michael D.; Batra, Surinder K.; Oupický, David
Abstract: Pancreatic cancer (PC) is one of the most aggressive malignancies due to intense desmoplasia, extreme hypoxia and inherent chemoresistance. Studies have implicated the expression of chemokine receptor CXCR4 and nuclear receptor co-activator-3 (NCOA3) in the development of desmoplasia and metastatic spread of PC. Using a series of polymeric CXCR4 antagonists (PCX), we optimized formulation of PCX/siNCOA3 polyplexes to simultaneously target CXCR4 and NCOA3 in PC. Cholesterol-modified PCX showed maximum CXCR4 antagonism, NCOA3 silencing and inhibition of PC cell migration in vitro . The optimized PCX/siNCOA3 polyplexes were used in evaluating antitumor and antimetastatic activity in orthotopic mouse model of metastatic PC. The polyplexes displayed significant inhibition of primary tumor growth, which was accompanied by a decrease in tumor necrosis and increased tumor perfusion. The polyplexes also showed significant antimetastatic effect and effective suppression of metastasis to distant organs. Overall, dual-function PCX/siNCOA3 polyplexes can effectively regulate tumor microenvironment to decrease progression and dissemination of PC.